The Dangers of Narcotics Crime and Transnational Network Threats: Child Empowerment and Protection Strategies in the Kupang–Semau Cluster - Fernando Silalahi; Marthen Boiliu (Multidisiplin Pengabdian Kepada Masyarakat, 2026)
This study examines a community engagement initiative conducted by the Graduate School of the Indonesian Christian University in collaboration with the Child Development Center (PPA) of the Kupang–Semau Cluster, aimed at addressing the growing risks of narcotics abuse and the threats posed by transnational narcotics networks. The program sought to enhance community awareness, with a particular focus on children and adolescents, regarding the physical, psychological, social, and legal consequences of narcotics use. Employing a participatory and educational approach, the initiative incorporated awareness-raising sessions, narcotics abuse prevention training, interactive discussion forums involving families and educators, and educational socialization on strategies for recognizing transnational criminal networks. The findings indicate a significant improvement in participants’ understanding of the dangers of narcotics and the mechanisms through which transnational networks operate within local contexts. Furthermore, the program highlights the critical role of multi-stakeholder collaboration particularly among educational institutions, religious organizations, and law enforcement agencies in strengthening child protection and community resilience against narcotics-related crimes. This study underscores the importance of community-based empowerment strategies as a preventive framework for safeguarding children and adolescents from the inﬂuence of narcotics and transnational criminal networks.